2019
DOI: 10.1371/journal.pone.0225575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antiretroviral resistance-associated mutation profile of treated and naive HIV-1 infected patients from the Northwest and Southwest regions of Cameroon

Abstract: BackgroundAntiretroviral therapy (ART) has improved the survival of HIV infected persons. However, rapid scale-up of ART and the high HIV-1 genetic variability, has greatly influenced the emergence of drug-resistant strains. This constitutes a potential threat to achieving the UNAIDS’ 90-90-90 goals by 2020. We investigated the prevalent HIV-1 genotypes, drug resistance-associated mutations and assessed some predictors of the occurrence of these mutations.MethodsThis was a hospital-based cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
(58 reference statements)
5
3
0
1
Order By: Relevance
“…Reverse transcriptase resistance mutations described in this study are in concordance with the previous study in Gabon [4] and Cameroon [27]. This study confirms that TDF has a high genetic barrier and therefore a low level of resistance as described in the literature [27] [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Reverse transcriptase resistance mutations described in this study are in concordance with the previous study in Gabon [4] and Cameroon [27]. This study confirms that TDF has a high genetic barrier and therefore a low level of resistance as described in the literature [27] [31].…”
Section: Discussionsupporting
confidence: 92%
“…Our studied population is characterized by the dominance of the circulating recombinant form (CRF) subtype. This CRF was previously described as a dominant subtype by previous publications in Gabon [3] [26] and Cameroon [27] [28]. A more recently conducted study in the southeast of Gabon (Franceville, provincial capital of Haut-Ogooué) shows the dominance of HIV-1 subtype "A" followed by "CRF" [4], in agreement with the previous studies conducted in the Republic of Congo, neighboring the province of Haut-Ogooué whose provincial capital is Franceville [29] [30].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the use of the coalescent model would allow the estimation of the effective population size (N e ), which in terms of phylodynamic is proportional to the effective number of infected population, 72 and the assessment of this parameter would help to identify the effect of the introduction of antiviral therapy in the epidemic curve and transmission dynamics. 73 Additionally, although antiviral resistance is more unlikely for an acute virus infection as COVID-19 than for a chronic infection like HIV, the example of anti-retroviral therapy (ART) has shown that evolutionary analysis can be used for the detection of adaptive mutations that if fixed can promote antiviral resistance. 74 This approach could also be used for timely detection of the emergence of drug-resistant strains and the need to switch to a new three-drug regimen (switching therapy).…”
Section: Use Of Phylodynamic In Antiviral Research For Treating Sars-mentioning
confidence: 99%
“… 74 This approach could also be used for timely detection of the emergence of drug-resistant strains and the need to switch to a new three-drug regimen (switching therapy). 73 Coupling these data with clinical and epidemiological metadata would help also to identify transmission networks associated with the emergence of resistance in case it happens. 74 …”
Section: Use Of Phylodynamic In Antiviral Research For Treating Sars-mentioning
confidence: 99%
“…Как известно, генотипы ВИЧ имеют свои молекулярно-генетические особенности, сказывающиеся, в том числе, и на чувствительности вируса к препаратам АРВТ [35]. Для генотипа CRF01_AE, наиболее распространенного в СРВ как по литературным данным, так и согласно полученным нами результатам, среди наиболее часто встречающихся мутаций описаны: L33F, M46I, M46L -ассоциированные с лекарственной устойчивостью к ингибиторам протеазы, M41L, A62V, M184V, T215Yк НИОТ, K103N, V108I, G190A -к ННИОТ [36,37].…”
unclassified